Aliran Filsafat Pendidikan Barat: Sebuah Telaah Pustaka - Yusuf, Muhammad; Somadi, Faqih; Haris, Abd; Anwar, Rosichin (CV. Creative Tugu Pena, 2023)
The writing of this research emerged because the progress of reasoning in schools continues to develop, so that educational philosophy is needed to form the foundation of a better world of education. This article discusses 1) what are the schools of western educational philosophy; 2) who are the figures in western educational philosophy. The method for researching western educational philosophy uses the library research method, namely by searching for theories about western educational philosophy and relevant theories. The results of the research in this paper are the classification of philosophy according to Brameld which contains perennial, essential, progressive and reconstructive. However, not only discussing what Brameld classifies, the author also adds discussion of humanist, existentialist and futurist schools. Keywords: Philosophy of Education, Western Philosophy of Education